Insight into the Mechanism of Axial Ligands Regulating the Catalytic Activity of Fe–N4 Sites for Oxygen Reduction Reaction. Issue 11 (1st February 2022) - Zhao, Kuang‐Min; Liu, Suqin; Li, Yu‐Yang; Wei, Xianli; Ye, Guanying; Zhu, Weiwei; Su, Yuke; Wang, Jue; Liu, Hongtao; He, Zhen; Zhou, Zhi‐You; Sun, Shi‐Gang
Abstract: Identifying the actual structure and tuning the catalytic activity of Fe–N4 ‐based moieties, well‐recognized high‐activity sites in the oxygen reduction reaction (ORR) are challenging problems. Herein, by using poly(iron phthalocyanine) (PFePc) as an Fe–N4 ‐based model electrocatalyst, a mechanistic insight into the effect of axial ligands on the ORR catalytic activity of Fe–N4 is provided and it is revealed that the ORR activity of Fe–N4 sites with OH desorption as a rate‐determining step is related to the energy level gap between the OH p x p y and Fe 3 d z 2, which can be tuned by regulating the field strength of the axial ligands. Thus, PFePc coordinated with a weak‐field ligand I − (PFePc‐I) with a low energy level of Fe 3 d z 2 exhibits high activity evidenced by an ORR half‐wave potential as high as 0.948 V versus RHE. This work develops a novel strategy for tuning the ORR activity of Fe–N4 and reveals the correlation between the electronic/geometric structure and catalytic activity of Fe–N4 . Abstract : Structure activity correlation of axial‐coordinated Fe–N4 sites in the oxygen reduction reaction (ORR) is unraveled by studying a series of axial‐coordinated poly(iron phthalocyanine) (PFePc). The energy gap (η DA ) between the Fe 3 d z 2 and OH p x /p y is proposed as a new descriptor for the ORR activity of the Fe–N4 sites with OH desorption as a rate‐determining step.